Phenological and yield components response of major exotic maize varieties to different levels of soil bulk densities - Khattak, Mansoor Khan; Hanif, Muhammad; Jaddon, Sulatn Akbar; Ul Haq, Inam; Uddin, Rafi (Universitas Sebelas Maret, 2022)
Maize is the second staple food and a major cereal crop in Pakistan, but its actual yield is 25-30% less than the potential because of high soil bulk densities. Three exotic maize varieties (Baber, Pioneer-30P45, and Syngenta-6621) were evaluated under the three different soil bulk densities of 1.00 - 1.30, 1.30 - 1.60, and 1.60- 1.90 g.cm-3. Nine treatments were replicated three times, making 27 pots experiments under complete randomized design were tested. Results showed that bulk density significantly (α < 0.05) affected all the parameters of the crops except the number of days to emergence. The fewest number of days to emergence (8.4), tasseling (60.9), silking (66.9), maturity (91.9), leaves per plant (6.3), as well as the lowest shoot thickness (0.49 cm) were obtained under the 1.00 - 1.30 g.cm-3 density. This density also produced the tallest plants (174.7 cm), highest stover (5938.7 kg ha-1), grain yields (1551 kg ha-1), and harvest index (21.9 %). Conversely, most days to emergence, tasseling, silking, and maturity occurred at the bulk density of 1.60 - 1.90 g.cm-3, which also produced the shortest plants and the lowest grain stover and grain yields as well as the harvest index. It was concluded that increasing bulk density levels increase the number of days to tasseling, silking, maturity, and leaves per plant and shoot thickness. Syngenta 6621 was found late in maturity among the hybrids but produced superior stover and grain yields.